2023
DOI: 10.7759/cureus.33600
|View full text |Cite
|
Sign up to set email alerts
|

Predictivity of CRP, Albumin, and CRP to Albumin Ratio on the Development of Intensive Care Requirement, Mortality, and Disease Severity in COVID-19

Abstract: Background: The C-reactive protein (CRP) to albumin ratio (CAR) is a new index calculated by dividing CRP by the albumin level. It has been claimed to have predictive value in determining morbidity and mortality in many critical diseases Aim: In this research, we aimed to elucidate the importance of CRP, albumin, and CAR as parameters that can predict the clinical course in COVID-19 patients.Materials & method: In this retrospective analysis, the clinical, laboratory, and radiological findings of patients over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
6
1
1
Order By: Relevance
“…These three markers have all been reported to be associated with the severity of COVID-19. [39][40][41][42][43][44] In our study, apart from CAR, we did not find a correlation between sTREM-1 and the severity of the disease. Therefore, the combination of CAR, HGB, and D-dimer yielded a strong predictive value for 28-day mortality in COVID-19 cases, with an AUC of 0.919 (95% CI: 0.857-0.981).…”
contrasting
confidence: 77%
“…These three markers have all been reported to be associated with the severity of COVID-19. [39][40][41][42][43][44] In our study, apart from CAR, we did not find a correlation between sTREM-1 and the severity of the disease. Therefore, the combination of CAR, HGB, and D-dimer yielded a strong predictive value for 28-day mortality in COVID-19 cases, with an AUC of 0.919 (95% CI: 0.857-0.981).…”
contrasting
confidence: 77%
“…Our results showed that cerebrovascular disease had the highest OR value of 2.76 (95 % CI: 1.65–4.62; I 2 = 44 %; p = 0.06) [ 19 , 21 , 28 , 31 33 , 38 40 , 44 , 45 ] despite the fact that no significant difference between patients with severe and non-severe cerebrovascular disease was reported after analysis. This risk is followed by chronic kidney disease (CKD), with an OR of 2.27 (95 % CI: 1.26–4.06]; I 2 = 96 %; P < 0.001) [ 15 , 18 , 19 , 22 , 24 , 26 35 , 37 , 38 , 42 , 44 , 45 ], hypertension with an OR of 2.22 (95% CI: 1.72–2.87; I 2 = 96 %; p < 0.001) [ 14 40 , 42 46 ] and coronary heart disease with an OR of 2.17 (95 % CI: 1.42–3.31; I 2 = 98 %; p < 0.001) [ 15 , 18 22 , 24 46 ]. Other significant judgment criteria for risk factors of the comorbidities involved in the severe form of COVID-19 included chronic obstructive pulmonary disease (COPD) (OR: 1.95, 95% CI: 1.22–3.09; I 2 =98%, p < 0.001) [ 14 , 15 , 19 23 , 25 28 , 30 32 , 34 36 , 38 42 , 44 , 45 ], diabetes mellitus (OR=1.81, 95% IC: 1.35–2.43; I 2 =97 %, p<0.001) [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Sarkar et al [ 20 ] evaluated the role of PLR in COVID-19 patients upon admission (14 studies; 2768 patients) for mortality, showing a WMD of 66.10 (95% CI: 47.75–84.44) with high heterogeneity (I2 = 89%) and low-quality evidence; a meta-analysis of 71 studies found no association for PLR with a poor prognosis in terms of mortality [ 21 ]. Moreover, a retrospective study evaluated the role of the CRP to serum albumin ratio in 272 COVID-19 patients in terms of mortality, finding an optimal cut-off above 21.5 (c-statistic of 0.72; 95% CI 0.66–0.77) [ 22 ], whereas another study that involved 3471 patients showed an optimal cut-off above 25 to be associated with mortality (OR, 1.47; 95% CI 1.19–1.82) [ 23 ]. A meta-analysis conducted by Zavalaga-Zegarra et al [ 24 ] evaluated the potential association of the CPR to albumin ratio in terms of mortality in 17 studies (7164 COVID-19 patients), finding higher values in non-survivors (MD: 2.59; 95% CI: 1.95–3.23) with severe heterogeneity (I2 = 92%).…”
Section: Discussionmentioning
confidence: 99%